Configuration‐Dependent Liquid Crystal and Gel Behaviors of Tetraphenylethene‐Containing Main‐Chain Copolyesters. Issue 18 (15th May 2022) - Wang, Jing; Wang, Tian; Jiang, Qian; Zhang, Yuping; Qiu, Yuan; Wang, Hong; Yin, Guochuan; Liao, Yonggui; Xie, Xiaolin
Abstract: The construction of aggregation‐induced emission‐active (AIE‐active) gelators with liquid crystal properties remains a challenge. Moreover, the effects of AIE configuration on liquid crystal, gel and AIE behaviors in one system are unclear. Herein, two main‐chain liquid crystalline copolyester gelators with a single configuration of AIEgen TPE, mesogen biphenyl, and pendent amide groups are synthesized through melt polycondensation. Both copolyesters display smectic phase, while E‐P20 possesses a wider temperature range of liquid crystal and a narrower layer distance owing to the more serious nonlinear "defect" of Z‐TPE than E‐TPE units. In addition, E‐P20 and Z‐P20 can form AIE‐active gels with the minimum gelation concentration (MGC) values of 10 and 4 wt% in ethyl acetate mainly via hydrogen bonds between the pendent amide groups, respectively. These AIE‐active gels show potential applications in temperature sensor, information storage, and so on. Abstract : Main‐chain liquid crystalline copolyesters with single‐configurational TPE, mesogen biphenyl and pendent amide groups display smectic phases in bulk and organogels in ethyl acetate. The configuration of TPE influences the smectic layer distances and the gelation abilities due to the more serious nonlinear "defect" of Z‐TPE than E‐TPE units.